2019
DOI: 10.1021/acs.inorgchem.9b00502
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Zeolitic Transition Metal Oxides Based on ε-Keggin Units for Selective Oxidation

Abstract: The design and development of zeolitic transition metal oxides for selective oxidation are interesting due to the combination of the redox properties and microporosities. Redoxactive zeolitic transition metal oxides based on ε-Keggin iron molybdates were synthesized. O 2 can be activated by the materials via an electron-transfer-based process, and the materials can be oxidized even at room temperature. The materials are oxidized and reduced reversibly while the crystal structures are maintained. V is uniformly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…Furthermore, ion‐exchange was able to replace the cation species of the material, which would change the property of the material. According to the previous study, Fe‐exchange would enable the material for the O 2 activation [13] . Herein, we found that introducing Fe by the ion‐exchange process would enhance the catalytic activity of the material.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…Furthermore, ion‐exchange was able to replace the cation species of the material, which would change the property of the material. According to the previous study, Fe‐exchange would enable the material for the O 2 activation [13] . Herein, we found that introducing Fe by the ion‐exchange process would enhance the catalytic activity of the material.…”
Section: Resultsmentioning
confidence: 58%
“…NH 4 MoFeO was able to activate O 2 at room temperature [13] . O 2 adsorbed in NH 4 MoFeO with oxidation of Mo and Fe during the adsorption.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations